Fiber battery and preparation method and application thereof

By using a helical structure and a specific proportion of manganese-based materials in flexible zinc ion batteries, the problem of low discharge specific capacity of the manganese-based material positive electrode battery is solved, and a higher discharge specific capacity and performance improvement is achieved.

CN119400979AActive Publication Date: 2025-02-07SUN YAT SEN UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411477152.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

In the prior art, the discharge specific capacity of flexible zinc ion batteries with manganese-based materials as the positive electrode materials is relatively low, which limits its application in wearable smart electronic products.

Method used

The structure of a spiral positive electrode nested in the spiral negative electrode, and a specific proportion of manganese-based materials of manganese dioxide, conductive agents and binders are coated on the surface of the positive electrode to increase the contact between the manganese-based materials and the solid electrolyte. Area, reduce the fall of the interface mask of active substances and solid electrolytes.

Benefits of technology

By improving the adhesion of manganese-based materials and fully exerting their role, the discharge specific capacity of fiber batteries is significantly improved, thereby improving the performance of flexible zinc ion batteries with manganese-based materials as the positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400979A_ABST
    Figure CN119400979A_ABST
Patent Text Reader

Abstract

The invention discloses a fiber battery and a preparation method and application thereof, the fiber battery comprises a positive electrode, a negative electrode and a solid electrolyte, the solid electrolyte wraps the positive electrode and the negative electrode, the positive electrode and the negative electrode are spiral, the positive electrode is nested in the negative electrode, the positive electrode is a positive wire with a manganese-based material on the surface, and the negative electrode is a negative wire with a manganese-based material on the surface. The negative electrode is a negative electrode wire of which the surface is provided with metal zinc; and the manganese-based material contains manganese dioxide, a conductive agent and a binder. According to the fiber battery disclosed by the invention, the contact area between the manganese-based material and the solid electrolyte can be increased by using the structure that the spiral positive electrode is nested in the spiral negative electrode and the specific manganese-based material, so that a large amount of manganese-based material is stably adhered to the surface of the positive wire; the active substance and the solid electrolyte interface film are reduced or prevented from falling off from the positive electrode, so that the manganese-based material fully plays the role, the specific discharge capacity of the fiber battery can be improved, and the specific discharge capacity of the flexible zinc ion battery taking the manganese-based material as the positive electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and more specifically, to a fiber battery and a preparation method and application thereof. Background Art

[0002] Wearable smart electronic products bring great convenience to human beings with their infinite possibilities, and they are likely to become an indispensable part of people's lives in the future. For wearable smart electronic products, the use of flexible batteries with high specific capacity, long cycle life and high safety is one of the most important links in its practical application. As one of the flexible batteries, flexible zinc-ion batteries have attracted extensive attention and research due to their rich zinc reserves, low redox potential, high theoretical capacity and high safety of the metal zinc negative electrode. At present, researchers and scientists have developed a variety of positive electrode materials for flexible zinc-ion batteries, such as manganese-based materials, vanadium-based materials, cobalt-based materials and Prussian blue analogs, etc. Among them, manganese-based materials are considered to be one of the most promising positive electrode materials for flexible zinc-ion batteries due to their high theoretical capacity, low cost and environmental friendliness, and have also been promoted and applied. However, the discharge specific capacity of flexible zinc-ion batteries using manganese-based materials as positive electrode materials is low, which to a certain extent restricts the promotion and application of flexible zinc-ion batteries.

[0003] Therefore, it is of great significance to develop a fiber battery to improve the discharge specific capacity of flexible zinc-ion batteries with manganese-based materials as positive electrode materials. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of low discharge specific capacity of flexible zinc ion batteries using manganese-based materials as positive electrode materials in the prior art, and to provide a fiber battery and a preparation method and application thereof.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In the first aspect, the present invention provides a fiber battery, comprising a positive electrode, a negative electrode and a solid electrolyte, wherein the solid electrolyte wraps the positive electrode and the negative electrode, the positive electrode and the negative electrode are both spiral in shape, the positive electrode is nested in the negative electrode, the positive electrode is a positive electrode wire with a manganese-based material on the surface, the negative electrode is a negative electrode wire with metallic zinc on the surface, and the manganese-based material contains manganese dioxide, a conductive agent, and a binder.

[0007] The fiber battery of the present invention can improve the discharge specific capacity of a flexible zinc ion battery using a manganese-based material as a positive electrode material.

[0008] Specifically, the fiber battery of the present invention can increase the contact area between the manganese-based material and the solid electrolyte by using a structure in which the spiral positive electrode is nested in the spiral negative electrode and a specific manganese-based material, so that a large amount of manganese-based material can be stably adhered to the surface of the positive electrode wire, reduce or prevent the active material and the solid electrolyte interface film (SEI) from falling off the positive electrode, and make the manganese-based material fully play its role, which is helpful to improve the discharge specific capacity of the fiber battery, that is, it is conducive to improving the discharge specific capacity of the flexible zinc ion battery with the manganese-based material as the positive electrode material. In addition, the structure in which the spiral positive electrode is nested in the spiral negative electrode improves the discharge specific capacity of the fiber battery by promoting the manganese-based material to play its role.

[0009] The solid electrolytes commonly used in the art can be used in the present invention.

[0010] Preferably, the solid electrolyte contains guar gum, zinc salt and manganese salt.

[0011] More preferably, the zinc salt is at least one of zinc sulfate (ZnSO4), zinc chloride and zinc nitrate.

[0012] More preferably, the manganese salt is at least one of manganese sulfate (MnSO4), manganese chloride and manganese nitrate.

[0013] Preferably, the manganese-based material contains manganese dioxide, a conductive agent and a binder in a mass ratio of (6-8):(1-2):(1-2).

[0014] More preferably, the manganese-based material contains manganese dioxide, a conductive agent, and a binder in a mass ratio of (7-8):(1-2):1.

[0015] More preferably, the manganese-based material contains manganese dioxide, a conductive agent, and a binder in a mass ratio of 7:2:1.

[0016] The fiber battery of the present invention uses a specific proportion of manganese dioxide, a conductive agent, and a binder, so that the manganese dioxide and the conductive agent are evenly distributed on the surface of the positive electrode wire, and a conductive network is formed by contact between them, which helps to further improve the discharge specific capacity of the fiber battery; at the same time, the specific proportion of manganese dioxide, the conductive agent, and the binder can further increase the adhesion of the manganese-based material, so that it can adhere to the surface of the positive electrode wire more stably, further reduce or prevent the active substance and the solid electrolyte interface film (SEI) from falling off from the positive electrode, so that the manganese-based material can further fully play its role, thereby further improving the discharge specific capacity of the fiber battery; that is, it is conducive to further improving the discharge specific capacity of the flexible zinc ion battery with manganese-based material as the positive electrode material.

[0017] The conductive agents and adhesives commonly used in the art can be used in the present invention.

[0018] Preferably, the conductive agent is at least one of carbon nanotubes, graphene, Super P, and acetylene black.

[0019] More preferably, the carbon nanotube is at least one of single-walled carbon nanotube, double-walled carbon nanotube and multi-walled carbon nanotube.

[0020] More preferably, the carbon nanotube is at least one of hydroxylated carbon nanotube, carboxylated carbon nanotube and amino carbon nanotube.

[0021] Preferably, the binder is at least one of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), and polyacrylic acid (PAA).

[0022] Preferably, the manganese-based material loading per unit area of ​​the positive electrode wire is 0.15-0.4 mg / cm 2 .

[0023] More preferably, the manganese-based material loading per unit area of ​​the positive electrode wire is 0.15 mg / cm 2 , 0.16mg / cm 2 , 0.17mg / cm 2 , 0.18mg / cm 2 、0.19mg / cm 2 , 0.2mg / cm 2 , 0.21mg / cm 2 , 0.22mg / cm 2 , 0.23mg / cm 2 , 0.24mg / cm 2 , 0.25mg / cm 2 , 0.26mg / cm 2 , 0.27mg / cm 2 、0.28mg / cm 2 , 0.29mg / cm 2 , 0.3mg / cm 2 , 0.31mg / cm 2 , 0.32mg / cm 2 , 0.33mg / cm 2 , 0.34mg / cm 2 , 0.35mg / cm 2 , 0.36mg / cm 2 , 0.37mg / cm 2 、0.38mg / cm 2 , 0.39mg / cm 2 , 0.4mg / cm 2 The range value of one or both of them.

[0024] More preferably, the manganese-based material loading per unit area of ​​the positive electrode wire is 0.18-0.38 mg / cm 2 .

[0025] Preferably, the metal zinc loading per unit area of ​​the negative electrode wire is 3.0-20.0 mg / cm 2 .

[0026] More preferably, the metal zinc loading per unit area of ​​the negative electrode wire is 3.0 mg / cm 2 、3.5mg / cm 2 、3.6mg / cm 2 , 4.0mg / cm 2 4.4mg / cm 2 , 4.5mg / cm 2 , 5.0mg / cm 2 , 5.5mg / cm 2 、6.0mg / cm 2 、7.0mg / cm 2 、8.0mg / cm 2 、9.0mg / cm 2 、9.5mg / cm 2 、10.0mg / cm 2 、11.0mg / cm 2 、12.0mg / cm 2 、13.0mg / cm 2 、14.0mg / cm 2 、15.0mg / cm 2 、16.0mg / cm 2 、17.0mg / cm 2 、17.7mg / cm 2 、18.0mg / cm 2 、18.5mg / cm 2 、19.0mg / cm 2 、20.0mg / cm 2 The range value of one or both of them.

[0027] More preferably, the metal zinc loading per unit area of ​​the negative electrode wire is 4.0-18.0 mg / cm 2 , specifically 4.0-9.5mg / cm 2 .

[0028] Preferably, the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is 0.2:(4.0-18.0).

[0029] In the present invention, the specific ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire can increase the discharge capacity of the fiber battery, that is, it is beneficial to increase the discharge capacity of the flexible zinc ion battery with manganese-based material as the positive electrode material.

[0030] When the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is too large, that is, the metal zinc loading per unit area of ​​the negative electrode wire is too low, the active substance of the positive electrode cannot fully react, resulting in a decrease in the discharge specific capacity of the fiber battery; when the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is too small, that is, the metal zinc loading per unit area of ​​the negative electrode wire is too high, the metal zinc layer on the surface of the negative electrode wire is thicker, and the metal zinc at the bottom cannot fully contact with the solid electrolyte, resulting in a smaller discharge specific capacity of the fiber battery.

[0031] More preferably, the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is 0.2:(4.0-9.5).

[0032] Preferably, the material of the positive electrode wire and / or the negative electrode wire is at least one of stainless steel and carbon fiber.

[0033] In a second aspect, the present invention provides a method for preparing a fiber battery, comprising the following steps:

[0034] S1. Coating and / or spraying a manganese-based material on the surface of the positive electrode wire to obtain a positive electrode for standby use;

[0035] S2. electroplating metal zinc on the surface of the negative electrode wire to obtain a negative electrode for standby use;

[0036] S3. Wrap the positive electrode and the negative electrode with a solid electrolyte, and embed the positive electrode in the negative electrode to obtain a fiber battery.

[0037] All electroplating solutions used for electroplating metal zinc in the art can be used in the present invention. For example, in step S2, the electroplating solution for electroplating metal zinc contains zinc sulfate, sodium sulfate, and boric acid.

[0038] Preferably, in step S2, the electroplating time of the electroplated metal zinc is ≥5 min.

[0039] More preferably, in step S2, the electroplating time of the metal zinc is within the range of one or any two of 5 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min, 28 min, and 30 min.

[0040] More preferably, the electroplating time of the electroplated metal zinc is 5-30 minutes, specifically 8-30 minutes.

[0041] In a third aspect, the present invention provides an application of a fiber battery in a wearable smart electronic product.

[0042] Wearable smart electronic products in the art can be used in the present invention, such as an in-situ monitoring device with hydrogel on the surface of a fiber battery, etc.

[0043] In a fourth aspect, the present invention provides an in-situ monitoring device, comprising a fiber battery and a hydrogel, wherein the hydrogel is provided on the surface of the fiber battery.

[0044] The in-situ monitoring device of the present invention uses a temperature-sensitive or strain-sensitive hydrogel as a sensing layer, and monitors the temperature or deformation of the fiber battery in real time by monitoring the resistance change of the hydrogel. Since the temperature change and deformation during the operation of the battery are important factors affecting the battery life and safety, the in-situ monitoring device can be used to perform non-destructive and real-time monitoring of the fiber battery, which can provide a reliable solution for the management of battery life and the protection of safety.

[0045] Preferably, the preparation method of the hydrogel is:

[0046] (1) mixing polyvinyl alcohol, carbon nanotubes and water to obtain solution A;

[0047] (2) mixing chitosan, acetic acid and water to obtain solution B;

[0048] (3) Mix solutions A and B and let them stand to form a gel to obtain a hydrogel.

[0049] More preferably, in step (1), the mass ratio of polyvinyl alcohol, carbon nanotubes and water is (2-6):(0.1-0.3):20.

[0050] More preferably, in step (2), the mass ratio of chitosan, acetic acid and water is (0.4-0.8):(0.6-0.9):(20-22).

[0051] Preferably, the thickness of the hydrogel is ≥0.8 mm.

[0052] More preferably, the thickness of the hydrogel is 0.8-2.8 mm.

[0053] More preferably, the thickness of the hydrogel is 0.8-1.6 mm.

[0054] In the present invention, the in-situ monitoring device with a hydrogel of a specific thickness has better sensitivity, can detect the temperature or deformation of the fiber battery more accurately and in real time, and also has a longer service life.

[0055] In a fifth aspect, the present invention provides a method for preparing an in-situ monitoring device, comprising the following steps:

[0056] By wrapping the fiber battery with hydrogel, an in-situ monitoring device is obtained.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] The fiber battery of the present invention can improve the discharge specific capacity of a flexible zinc ion battery using a manganese-based material as a positive electrode material.

[0059] Specifically, the fiber battery of the present invention can increase the contact area between the manganese-based material and the solid electrolyte by using a structure in which the spiral positive electrode is nested in the spiral negative electrode and a specific manganese-based material, so that a large amount of manganese-based material can be stably adhered to the surface of the positive electrode wire, reduce or prevent the active material and the solid electrolyte interface film (SEI) from falling off the positive electrode, and make the manganese-based material fully play its role, which is helpful to improve the discharge specific capacity of the fiber battery, that is, it is conducive to improving the discharge specific capacity of the flexible zinc ion battery with the manganese-based material as the positive electrode material. In addition, the structure in which the spiral positive electrode is nested in the spiral negative electrode improves the discharge specific capacity of the fiber battery by promoting the manganese-based material to play its role.

[0060] The fiber battery of the present invention uses a specific proportion of manganese dioxide, a conductive agent, and a binder, so that the manganese dioxide and the conductive agent are evenly distributed on the surface of the positive electrode wire, and a conductive network is formed by contact between them, which helps to further improve the discharge specific capacity of the fiber battery; at the same time, the specific proportion of manganese dioxide, the conductive agent, and the binder can further increase the adhesion of the manganese-based material, so that it can adhere to the surface of the positive electrode wire more stably, further reduce or prevent the active substance and the solid electrolyte interface film (SEI) from falling off from the positive electrode, so that the manganese-based material can further fully play its role, thereby further improving the discharge specific capacity of the fiber battery; that is, it is conducive to further improving the discharge specific capacity of the flexible zinc ion battery with manganese-based material as the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a schematic diagram of the structure of the fiber battery of Example 1;

[0062] Figure 2 This is a schematic diagram of the position relationship between the positive electrode and the negative electrode of the fiber battery of comparative example 3;

[0063] Figure 3 This is a schematic diagram of the position relationship between the positive electrode and the negative electrode of the fiber battery of Comparative Example 4;

[0064] Figure 4 This is a physical picture of the positive electrode of the fiber battery of comparative example 5;

[0065] Figure 5 This is a schematic diagram of the position relationship between the positive electrode and the negative electrode of the fiber battery of Comparative Example 6;

[0066] Figure 6 This is a schematic diagram of the structure of the in-situ monitoring device of Application Example 1;

[0067] Figure 7 This is a side view of the hydrogel in Application Example 1;

[0068] Figure 8 This is a side view of the hydrogel in Application Example 3;

[0069] Fig. 9 It is the rate performance diagram of Examples 1-2 and Comparative Example 1;

[0070] Fig.10 It is the rate performance diagram of Examples 1, 3-5 and Comparative Example 2;

[0071] In the figure: 1-positive electrode, 2-negative electrode, 3-solid electrolyte, 4-hydrogel. DETAILED DESCRIPTION

[0072] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0073] The experimental methods without specific conditions in the following examples, comparative examples, application examples and comparative application examples are generally carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.

[0074] In each embodiment, comparative example, application example and comparative application example of the present invention, the use of reagents is as follows:

[0075] Carbon nanotubes (conductive agent), hydroxylated multi-walled carbon nanotubes, length: 0.5-2 μm, item number: 100788, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;

[0076] Polyvinylidene fluoride (PVDF, binder), catalog number: 768740, Shanghai MacLean Biochemical Technology Co., Ltd.;

[0077] Guar gum, product number: G109238, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0078] Polyvinyl alcohol, product number: S30196, Shanghai Yuanye Biotechnology Co., Ltd.;

[0079] Chitosan, product number: C299272, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0080] Example 1

[0081] This embodiment provides a fiber battery, and its structural schematic diagram is as follows Figure 1As shown, it includes a positive electrode, a negative electrode and a solid electrolyte, the solid electrolyte wraps the positive electrode and the negative electrode, the positive electrode and the negative electrode are both spiral-shaped, the positive electrode is nested in the negative electrode, the positive electrode is a positive electrode wire with a manganese-based material on the surface, and the negative electrode is a negative electrode wire with metal zinc on the surface, and the manganese-based material contains manganese dioxide, carbon nanotubes (conductive agent), and polyvinylidene fluoride (PVDF, binder) in a mass ratio of 7:2:1;

[0082] The manganese-based material loading per unit area of ​​the positive electrode wire is 0.2 mg / cm 2 The metal zinc loading per unit area of ​​the negative electrode wire is 9.0 mg / cm 2 ; The material of the positive electrode wire and the negative electrode wire is 304 stainless steel; the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is 0.2:9.0; the solid electrolyte contains guar gum, zinc sulfate (ZnSO4) and manganese sulfate (MnSO4);

[0083] The method for preparing the fiber battery comprises the following steps:

[0084] S1. Mix manganese dioxide, carbon nanotubes and polyvinylidene fluoride in a mass ratio of 7:2:1 to obtain a manganese dioxide mixture; take 0.1g of the manganese dioxide mixture and dissolve it in 0.5mL N-methylpyrrolidone (NMP) to obtain a manganese-based material; weigh the mass m0 of the positive electrode wire before coating; coat the manganese-based material on the surface of the spiral positive electrode wire (304 stainless steel spring, with a spring wire diameter of 0.2mm, an outer diameter of the spring coil of 1mm, a spring length of 25mm, and a number of turns of 55) and place it in a 70℃ vacuum drying oven for 2h; weigh the mass m of the positive electrode wire after drying, calculate the surface area S of the positive electrode wire according to the inner diameter and length of the positive electrode wire, and take the manganese-based material loading amount (m-m0) / S=0.2mg / cm 2 The positive electrode is reserved;

[0085] S2. Immerse the spiral negative electrode wire (304 stainless steel spring, with a spring wire diameter of 0.2 mm, an outer diameter of the spring coil of 2 mm, a spring length of 25 mm, and 23 turns of the spring) in 25 mL of electroplating solution [0.43 mol / L zinc sulfate (ZnSO4), 0.88 mol / L sodium sulfate (Na2SO4), 0.32 mol / L boric acid (H3BO3)] at 40 mA / cm 2 , electroplating for 15 min at a current of 36.28 mA to electroplate metal zinc on the surface of the negative electrode wire, washing with deionized water, and drying in a vacuum drying oven at room temperature for 2 h to obtain the negative electrode for standby use;

[0086] S3. Add 0.6g guar gum, 0.02mol zinc sulfate (ZnSO4) and 0.001mol manganese sulfate (MnSO4) into 10mL water to obtain a solid electrolyte solution; first soak the positive electrode prepared in step S1 in the solid electrolyte solution for 1min, take it out and let it stand for 0.5h, then nest the positive electrode in the negative electrode and soak it in the remaining solid electrolyte solution, let it stand for 1h to form a gel, so that the solid electrolyte wraps the positive and negative electrodes, and encapsulates them to obtain a fiber battery.

[0087] Example 2 and Comparative Example 1

[0088] Example 2 and Comparative Example 1 provide different fiber batteries. The difference between Example 2 and Comparative Example 1 is that the mass ratios of manganese dioxide, carbon nanotubes, and polyvinylidene fluoride in the manganese-based material are different. The rest are consistent with Example 1, as shown in the following table:

[0089] Table 1 Mass ratio of manganese dioxide, carbon nanotubes and polyvinylidene fluoride in manganese-based materials of Examples 1-2 and Comparative Example 1

[0090] Mass ratio of manganese dioxide, carbon nanotubes and polyvinylidene fluoride Example 1 7:2:1 Example 2 8:1:1 Comparative Example 1 6:2:2

[0091] Examples 3-5 and Comparative Example 2

[0092] Embodiments 3-5 and Comparative Example 2 provide different fiber batteries, which differ from Embodiment 1 in that the metal zinc loading per unit area of ​​the negative electrode wire is different, that is, the electroplating time in step S2 is different, and the rest is consistent with Embodiment 1, as shown in the following table:

[0093] Table 2 Metal zinc loading per unit area of ​​negative electrode wire in Examples 1, 3-5 and Comparative Example 2

[0094]

[0095] Comparative Example 3

[0096] This comparative example provides a fiber battery, which differs from Example 1 in that the positive electrode and the negative electrode are parallel to each other, as shown in the schematic diagram. Figure 2 As shown, the positive electrode of Example 1 is not nested in the negative electrode, and the rest is consistent with Example 1, as follows:

[0097] The fiber battery includes a positive electrode, a negative electrode and a solid electrolyte, wherein the solid electrolyte wraps the positive electrode and the negative electrode, the positive electrode and the negative electrode are both spiral in shape, the positive electrode is parallel to the negative electrode, the positive electrode is a positive electrode wire with a manganese-based material on the surface, and the negative electrode is a negative electrode wire with metal zinc on the surface, and the manganese-based material contains manganese dioxide, carbon nanotubes (conductive agent), and polyvinylidene fluoride (PVDF, binder) in a mass ratio of 7:2:1;

[0098] The manganese-based material loading per unit area of ​​the positive electrode wire is 0.2 mg / cm 2 The metal zinc loading per unit area of ​​the negative electrode wire is 9.0 mg / cm 2 ; The material of the positive electrode wire and the negative electrode wire is 304 stainless steel; the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is 0.2:9.0; the solid electrolyte contains guar gum, zinc sulfate (ZnSO4) and manganese sulfate (MnSO4);

[0099] The method for preparing the fiber battery comprises the following steps:

[0100] S1. Mix manganese dioxide, carbon nanotubes and polyvinylidene fluoride in a mass ratio of 7:2:1 to obtain a manganese dioxide mixture; take 0.1g of the manganese dioxide mixture and dissolve it in 0.5mL N-methylpyrrolidone (NMP) to obtain a manganese-based material; weigh the mass m0 of the positive electrode wire before coating; coat the manganese-based material on the surface of the spiral positive electrode wire (304 stainless steel spring, with a spring wire diameter of 0.2mm, an outer diameter of the spring coil of 1mm, a spring length of 25mm, and a number of turns of 55) and place it in a 70℃ vacuum drying oven for 2h; weigh the mass m of the positive electrode wire after drying, calculate the surface area S of the positive electrode wire according to the inner diameter and length of the positive electrode wire, and take the manganese-based material loading amount (m-m0) / S=0.2mg / cm 2 The positive electrode is reserved;

[0101] S2. Immerse the spiral negative electrode wire (304 stainless steel spring, with a spring wire diameter of 0.2 mm, an outer diameter of the spring coil of 2 mm, a spring length of 25 mm, and 23 turns of the spring) in 25 mL of electroplating solution [0.43 mol / L zinc sulfate (ZnSO4), 0.88 mol / L sodium sulfate (Na2SO4), 0.32 mol / L boric acid (H3BO3)] at 40 mA / cm 2 , electroplating for 15 min at a current of 36.28 mA to electroplate metal zinc on the surface of the negative electrode wire, washing with deionized water, and drying in a vacuum drying oven at room temperature for 2 h to obtain the negative electrode for standby use;

[0102] S3. Add 0.6 g guar gum, 0.02 mol zinc sulfate (ZnSO4) and 0.001 mol manganese sulfate (MnSO4) to 10 mL water to obtain a solid electrolyte solution; then insert the positive electrode and the negative electrode, and make the positive electrode and the negative electrode parallel (such as Figure 2 As shown), let it stand for 1 hour to form a gel, so that the solid electrolyte wraps the positive electrode and the negative electrode, and then encapsulates to obtain a fiber battery.

[0103] Comparative Example 4

[0104] This comparative example provides a fiber battery, which differs from Example 1 in that the positive electrode and the negative electrode are parallel to each other, and the shapes of the positive electrode and the negative electrode are both linear, as shown in the schematic diagram. Figure 3 As shown, the positive electrode of Example 1 is not nested in the negative electrode, and the shapes of the positive electrode and the negative electrode are both spiral, and the rest are consistent with Example 1, as follows:

[0105] The fiber battery includes a positive electrode, a negative electrode and a solid electrolyte, wherein the solid electrolyte wraps the positive electrode and the negative electrode, the positive electrode and the negative electrode are both linear in shape, the positive electrode is parallel to the negative electrode, the positive electrode is a positive electrode wire with a manganese-based material on the surface, and the negative electrode is a negative electrode wire with metal zinc on the surface, and the manganese-based material contains manganese dioxide, carbon nanotubes (conductive agent), and polyvinylidene fluoride (PVDF, binder) in a mass ratio of 7:2:1;

[0106] The manganese-based material loading per unit area of ​​the positive electrode wire is 0.2 mg / cm 2 The metal zinc loading per unit area of ​​the negative electrode wire is 9.0 mg / cm 2 ; The material of the positive electrode wire and the negative electrode wire is 304 stainless steel; the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is 0.2:9.0; the solid electrolyte contains guar gum, zinc sulfate (ZnSO4) and manganese sulfate (MnSO4);

[0107] The method for preparing the fiber battery comprises the following steps:

[0108] S1. Mix manganese dioxide, carbon nanotubes and polyvinylidene fluoride in a mass ratio of 7:2:1 to obtain a manganese dioxide mixture; take 0.1g of the manganese dioxide mixture and dissolve it in 0.5mL N-methylpyrrolidone (NMP) to obtain a manganese-based material; weigh the mass m0 of the positive electrode wire before coating; coat the manganese-based material on the surface of a linear positive electrode wire (linear 304 stainless steel wire with an outer diameter of 0.2mm and a length of 25mm), and place it in a vacuum drying oven at 70°C for 2h; weigh the mass m of the positive electrode wire after drying, calculate the surface area S of the positive electrode wire according to the inner diameter and length of the positive electrode wire, and take the manganese-based material loading amount (m-m0) / S=0.2mg / cm 2 The positive electrode is reserved;

[0109] S2. Immerse the negative electrode wire (linear 304 stainless steel wire, with an outer diameter of 0.2 mm and a length of 25 mm) in 25 mL of electroplating solution [0.43 mol / L zinc sulfate (ZnSO4), 0.88 mol / L sodium sulfate (Na2SO4), 0.32 mol / L boric acid (H3BO3)] at 40 mA / cm 2, electroplating for 15 min at 6.28 mA current to electroplate metal zinc on the surface of the negative electrode wire, washing with deionized water, and drying in a vacuum drying oven at room temperature for 2 h to obtain the negative electrode for standby use;

[0110] S3. Add 0.6 g guar gum, 0.02 mol zinc sulfate (ZnSO4) and 0.001 mol manganese sulfate (MnSO4) to 10 mL water to obtain a solid electrolyte solution; then insert the positive electrode and the negative electrode, and make the positive electrode and the negative electrode parallel (such as Figure 3 As shown), let it stand for 1 hour to form a gel, so that the solid electrolyte wraps the positive electrode and the negative electrode, and then encapsulates to obtain a fiber battery.

[0111] Comparative Example 5

[0112] This comparative example provides a fiber battery, which differs from Example 1 in that the positional relationship between the positive electrode and the negative electrode is that the negative electrode is nested in the positive electrode, rather than the positive electrode being nested in the negative electrode in Example 1, and the rest is consistent with Example 1, as follows:

[0113] The fiber battery includes a positive electrode, a negative electrode and a solid electrolyte, wherein the solid electrolyte wraps the positive electrode and the negative electrode, the positive electrode and the negative electrode are both spiral-shaped, the negative electrode is nested in the positive electrode, the positive electrode is a positive electrode wire with a manganese-based material on the surface, and the negative electrode is a negative electrode wire with metal zinc on the surface, and the manganese-based material contains manganese dioxide, carbon nanotubes (conductive agent), and polyvinylidene fluoride (PVDF, binder) in a mass ratio of 7:2:1;

[0114] The manganese-based material loading per unit area of ​​the positive electrode wire is 0.2 mg / cm 2 The metal zinc loading per unit area of ​​the negative electrode wire is 9.0 mg / cm 2 ; The material of the positive electrode wire and the negative electrode wire is 304 stainless steel; the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is 0.2:9.0; the solid electrolyte contains guar gum, zinc sulfate (ZnSO4) and manganese sulfate (MnSO4);

[0115] The method for preparing the fiber battery comprises the following steps:

[0116] S1. Mix manganese dioxide, carbon nanotubes and polyvinylidene fluoride in a mass ratio of 7:2:1 to obtain a manganese dioxide mixture; take 0.1g of the manganese dioxide mixture and dissolve it in 0.5mL N-methylpyrrolidone (NMP) to obtain a manganese-based material; weigh the mass m0 of the positive electrode wire before coating; coat the manganese-based material on the surface of the spiral positive electrode wire (304 stainless steel spring, with a spring wire diameter of 0.2mm, an outer diameter of the spring coil of 2mm, a spring length of 25mm, and 23 turns of the spring), and place it in a 70℃ vacuum drying oven for 2h; weigh the mass m of the positive electrode wire after drying, calculate the surface area S of the positive electrode wire according to the inner diameter and length of the positive electrode wire, and take the manganese-based material loading amount (m-m0) / S=0.2mg / cm 2 The positive electrode is reserved;

[0117] S2. Immerse the spiral negative electrode wire (304 stainless steel spring, with a spring wire diameter of 0.2 mm, an outer diameter of the spring coil of 1 mm, a spring length of 25 mm, and a number of spring turns of 55) in 25 mL of electroplating solution [0.43 mol / L zinc sulfate (ZnSO4), 0.88 mol / L sodium sulfate (Na2SO4), 0.32 mol / L boric acid (H3BO3)] at 40 mA / cm 2 , electroplating for 15 min at a current of 43.38 mA to electroplate metal zinc on the surface of the negative electrode wire, washing with deionized water, and drying in a vacuum drying oven at room temperature for 2 h to obtain the negative electrode for standby use;

[0118] S3. Add 0.6g guar gum, 0.02mol zinc sulfate (ZnSO4) and 0.001mol manganese sulfate (MnSO4) to 10mL water to obtain a solid electrolyte solution; first soak the negative electrode prepared in step S2 in the solid electrolyte solution for 1min, take it out and let it stand for 0.5h, and then embed the negative electrode in the positive electrode. At this time, it is found that the negative electrode cannot be embedded in the positive electrode. The reason is: when the positive electrode is prepared by the coating method in step S1, Figure 4 As shown, the manganese-based material will penetrate into the interior of the 304 stainless steel spring, causing the interior of the 304 stainless steel spring to be filled with the manganese-based material, hindering the negative electrode from being embedded in the positive electrode, resulting in the inability to prepare a fiber battery with the negative electrode nested in the positive electrode.

[0119] Comparative Example 6

[0120] This comparative example provides a fiber battery, which is different from Example 1 in that the positive electrode and the negative electrode are intertwined, and the shapes of the positive electrode and the negative electrode are both linear, as shown in the schematic diagram. Figure 5 As shown, the positive electrode of Example 1 is not nested in the negative electrode, and the shapes of the positive electrode and the negative electrode are both spiral, and the rest are consistent with Example 1, as follows:

[0121] The fiber battery includes a positive electrode, a negative electrode and a solid electrolyte, wherein the solid electrolyte wraps the positive electrode and the negative electrode, the positive electrode and the negative electrode are both in a linear shape, the positive electrode and the negative electrode are intertwined, the positive electrode is a positive electrode wire with a manganese-based material on the surface, and the negative electrode is a negative electrode wire with metal zinc on the surface, and the manganese-based material contains manganese dioxide, carbon nanotubes (conductive agent), and polyvinylidene fluoride (PVDF, binder) in a mass ratio of 7:2:1;

[0122] The manganese-based material loading per unit area of ​​the positive electrode wire is 0.2 mg / cm 2 The metal zinc loading per unit area of ​​the negative electrode wire is 9.0 mg / cm 2 ; The material of the positive electrode wire and the negative electrode wire is 304 stainless steel; the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is 0.2:9.0; the solid electrolyte contains guar gum, zinc sulfate (ZnSO4) and manganese sulfate (MnSO4);

[0123] The method for preparing the fiber battery comprises the following steps:

[0124] S1. Mix manganese dioxide, carbon nanotubes and polyvinylidene fluoride in a mass ratio of 7:2:1 to obtain a manganese dioxide mixture; take 0.1g of the manganese dioxide mixture and dissolve it in 0.5mL N-methylpyrrolidone (NMP) to obtain a manganese-based material; weigh the mass m0 of the positive electrode wire before coating; coat the manganese-based material on the surface of a linear positive electrode wire (linear 304 stainless steel wire with an outer diameter of 0.2mm and a length of 25mm), and place it in a vacuum drying oven at 70°C for 2h; weigh the mass m of the positive electrode wire after drying, calculate the surface area S of the positive electrode wire according to the inner diameter and length of the positive electrode wire, and take the manganese-based material loading amount (m-m0) / S=0.2mg / cm 2 The positive electrode is reserved;

[0125] S2. Immerse the negative electrode wire (linear 304 stainless steel wire, with an outer diameter of 0.2 mm and a length of 25 mm) in 25 mL of electroplating solution [0.43 mol / L zinc sulfate (ZnSO4), 0.88 mol / L sodium sulfate (Na2SO4), 0.32 mol / L boric acid (H3BO3)] at 40 mA / cm 2 , electroplating for 15 min at 6.28 mA current to electroplate metal zinc on the surface of the negative electrode wire, washing with deionized water, and drying in a vacuum drying oven at room temperature for 2 h to obtain the negative electrode for standby use;

[0126] S3. Add 0.6g guar gum, 0.02mol zinc sulfate (ZnSO4) and 0.001mol manganese sulfate (MnSO4) to 10mL water to obtain a solid electrolyte solution; first soak the positive electrode and the negative electrode in the solid electrolyte solution for 1min, take them out and let them stand for 0.5h, and then make the positive and negative electrodes intertwine with each other. At this time, it is found that when the positive and negative electrodes are intertwined, Figure 5 As shown, the manganese-based material and solid electrolyte on the surface of the positive electrode were severely detached due to the entanglement between the positive and negative electrodes, causing the stainless steel wires of the positive and negative electrodes to be in direct contact, resulting in a short circuit in the fiber battery prepared using the mutually entangled positive and negative electrodes. Therefore, it is impossible to prepare a fiber battery with mutually entangled positive and negative electrodes.

[0127] Application Example 1

[0128] This application example provides an in-situ monitoring device, and its structural schematic diagram is as follows Figure 6 As shown, it includes the fiber battery and hydrogel prepared in Example 1, and the surface of the fiber battery is provided with hydrogel;

[0129] The method for preparing the above-mentioned in-situ monitoring device comprises the following steps:

[0130] (1) 4 g of polyvinyl alcohol, 0.15 g of carbon nanotubes and 20 mL of water were mixed and stirred at 120 °C for 2 h to obtain solution A;

[0131] (2) mixing 0.8 g of chitosan, 2.8 mL of 30% acetic acid aqueous solution and 20 mL of water, and stirring for 2 h to obtain solution B;

[0132] (3) Mix solutions A and B, pour into a mold with a thickness of 0.8 mm, and let stand at -20 ° C for 12 h to form a hydrogel with a thickness of 0.8 mm. Figure 7 As shown, the thickness of the hydrogel is evenly distributed;

[0133] (4) The hydrogel in step (3) wraps the fiber battery of Example 1 to obtain an in-situ monitoring device;

[0134] The mass ratio of polyvinyl alcohol, carbon nanotubes and water in step (1) is 4:0.15:20.

[0135] The mass ratio of chitosan, acetic acid and water in step (2) is 0.8:0.84:21.96,

[0136] In the present invention, the density of the acetic acid aqueous solution with a mass fraction of 30% and water are both considered to be 1 g / mL.

[0137] Application Example 2

[0138] This application example provides an in-situ monitoring device, which differs from application example 1 in that the thickness of the hydrogel is 1.6 mm, and the rest is consistent with embodiment 1, as follows:

[0139] The in-situ monitoring device comprises the fiber battery prepared in Example 1 and a hydrogel, wherein the surface of the fiber battery is provided with a hydrogel;

[0140] The method for preparing the above-mentioned in-situ monitoring device comprises the following steps:

[0141] (1) 4 g of polyvinyl alcohol, 0.15 g of carbon nanotubes and 20 mL of water were mixed and stirred at 120 °C for 2 h to obtain solution A;

[0142] (2) mixing 0.8 g of chitosan, 2.8 mL of 30% acetic acid aqueous solution and 20 mL of water, and stirring for 2 h to obtain solution B;

[0143] (3) Mixing solutions A and B, pouring into a mold with a thickness of 1.6 mm, and standing at -20°C for 12 h to form a hydrogel with a thickness of 1.6 mm. The thickness of the hydrogel is evenly distributed;

[0144] (4) The hydrogel in step (3) wraps the fiber battery of Example 1 to obtain an in-situ monitoring device;

[0145] The mass ratio of polyvinyl alcohol, carbon nanotubes and water in step (1) is 4:0.15:20.

[0146] The mass ratio of chitosan, acetic acid and water in step (2) is 0.8:0.84:21.96,

[0147] In the present invention, the density of the acetic acid aqueous solution with a mass fraction of 30% and water are both considered to be 1 g / mL.

[0148] Application Example 3

[0149] This application example provides an in-situ monitoring device, which differs from application example 1 in that the thickness of the hydrogel is 2.8 mm, and the rest is consistent with embodiment 1, as follows:

[0150] The in-situ monitoring device comprises the fiber battery prepared in Example 1 and a hydrogel, wherein the surface of the fiber battery is provided with a hydrogel;

[0151] The method for preparing the above-mentioned in-situ monitoring device comprises the following steps:

[0152] (1) 4 g of polyvinyl alcohol, 0.15 g of carbon nanotubes and 20 mL of water were mixed and stirred at 120 °C for 2 h to obtain solution A;

[0153] (2) mixing 0.8 g of chitosan, 2.8 mL of 30% acetic acid aqueous solution and 20 mL of water, and stirring for 2 h to obtain solution B;

[0154] (3) Mix solutions A and B, pour into a mold with a thickness of 2.8 mm, and let stand at -20 °C for 12 h to form a hydrogel with a thickness of 2.8 mm. Figure 8 As shown, the thickness of the hydrogel is evenly distributed;

[0155] (4) The hydrogel in step (3) wraps the fiber battery of Example 1 to obtain an in-situ monitoring device;

[0156] The mass ratio of polyvinyl alcohol, carbon nanotubes and water in step (1) is 4:0.15:20.

[0157] The mass ratio of chitosan, acetic acid and water in step (2) is 0.8:0.84:21.96,

[0158] In the present invention, the density of the acetic acid aqueous solution with a mass fraction of 30% and water are both considered to be 1 g / mL.

[0159] Application Example 4

[0160] This application example provides an in-situ monitoring device, comprising the fiber battery and hydrogel prepared in Example 1, wherein the surface of the fiber battery is provided with hydrogel;

[0161] The method for preparing the above-mentioned in-situ monitoring device comprises the following steps:

[0162] (1) 4 g of polyvinyl alcohol, 0.15 g of carbon nanotubes and 20 mL of water were mixed and stirred at 120 °C for 2 h to obtain solution A;

[0163] (2) mixing 0.8 g of chitosan, 2.8 mL of 30% acetic acid aqueous solution and 20 mL of water, and stirring for 2 h to obtain solution B;

[0164] (3) Mixing solutions A and B, pouring into a mold with a thickness of 0.3 mm, and standing at -20°C for 12 h to gel, to obtain a hydrogel with a thickness of 0.3 mm, and the thickness of the hydrogel is evenly distributed;

[0165] (4) The hydrogel in step (3) wraps the fiber battery of Example 1 to obtain an in-situ monitoring device;

[0166] The mass ratio of polyvinyl alcohol, carbon nanotubes and water in step (1) is 4:0.15:20.

[0167] The mass ratio of chitosan, acetic acid and water in step (2) is 0.8:0.84:21.96,

[0168] In the present invention, the density of the acetic acid aqueous solution with a mass fraction of 30% and water are both considered to be 1 g / mL.

[0169] It is worth noting that the in-situ monitoring device prepared in this application example is easily damaged due to the thin thickness of the hydrogel used, which reduces the service life of the in-situ monitoring device.

[0170] In addition, in order to ensure the service life of the in-situ monitoring device, the thickness of the hydrogel is generally required to be at least 0.6 mm.

[0171] Performance Testing

[0172] 1. Conduct discharge capacity test on the fiber batteries of various embodiments and comparative examples:

[0173] At 25°C, the discharge capacity of the fiber batteries of various embodiments and comparative examples at different current densities was tested using a Blue Electric Battery Test System (Model: CT3002A, Wuhan Blue Electric Electronics Co., Ltd.); during the test, the fiber battery was activated with a small current density of 0.1 A / g. Since the first charge and discharge cycle after small current activation and change of current density is unstable, the discharge capacity data of the second cycle at a current density of 0.2 A / g was taken as the discharge capacity data of the fiber batteries of various embodiments and comparative examples. The experimental results are shown in Table 3:

[0174] Table 3 Discharge specific capacity of fiber batteries of various embodiments and comparative examples

[0175]

[0176]

[0177] Fig. 9 is the rate performance diagram of Examples 1-2 and Comparative Example 1, Fig.10 It is the rate performance diagram of Examples 1, 3-5 and Comparative Example 2.

[0178] From Table 3 and Figure 9-10 It can be seen that the fiber battery of the present invention can improve the discharge specific capacity of the flexible zinc ion battery using manganese-based materials as the positive electrode material.

[0179] Specifically, the fiber battery of the present invention can increase the contact area between the manganese-based material and the solid electrolyte by using a structure in which the spiral positive electrode is nested in the spiral negative electrode and a specific manganese-based material, so that a large amount of manganese-based material can be stably adhered to the surface of the positive electrode wire, reduce or prevent the active material and the solid electrolyte interface film (SEI) from falling off the positive electrode, and make the manganese-based material fully play its role, which is helpful to improve the discharge specific capacity of the fiber battery, that is, it is conducive to improving the discharge specific capacity of the flexible zinc ion battery with the manganese-based material as the positive electrode material. In addition, the structure in which the spiral positive electrode is nested in the spiral negative electrode improves the discharge specific capacity of the fiber battery by promoting the manganese-based material to play its role.

[0180] In particular, it can be seen from Examples 1-2 and Comparative Example 1 that the fiber battery of the present invention can make manganese dioxide and the conductive agent evenly distributed on the surface of the positive electrode wire by using a specific proportion of manganese dioxide, a conductive agent, and a binder, and form a conductive network through contact with each other, which helps to further improve the discharge specific capacity of the fiber battery; at the same time, the specific proportion of manganese dioxide, the conductive agent, and the binder can further increase the adhesion of the manganese-based material, so that it can adhere to the surface of the positive electrode wire more stably, further reduce or prevent the active substance and the solid electrolyte interface film (SEI) from falling off from the positive electrode, so that the manganese-based material can further fully play its role, thereby further improving the discharge specific capacity of the fiber battery; that is, it is conducive to further improving the discharge specific capacity of the flexible zinc ion battery with manganese-based material as the positive electrode material.

[0181] In addition, in the present invention, the specific ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire can increase the discharge capacity of the fiber battery, that is, it is beneficial to increase the discharge capacity of the flexible zinc-ion battery with manganese-based material as the positive electrode material.

[0182] It can be seen from Examples 1, 3-5 and Comparative Example 2 that when the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is too large, that is, the metal zinc loading per unit area of ​​the negative electrode wire is too low, the active material of the positive electrode cannot fully react, resulting in a decrease in the discharge specific capacity of the fiber battery; when the ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is too small, that is, the metal zinc loading per unit area of ​​the negative electrode wire is too high, the metal zinc layer on the surface of the negative electrode wire is thicker, and the metal zinc at the bottom cannot fully contact with the solid electrolyte, resulting in a smaller discharge specific capacity of the fiber battery.

[0183] 2. Conduct sensitivity tests on the in-situ monitoring devices of each application example:

[0184] At 25°C, the fiber battery was charged and discharged using a Blue Electric battery test system (model: CT3002A, Wuhan Blue Electric Electronics Co., Ltd.). A high-precision current and voltage test source (Keithley 2635B) was used to monitor the resistance change of the sensing layer of each application example during the battery charging and discharging process. The resistance change rate ΔR / R0 during the charging and discharging process was calculated. R0 is the initial resistance of the sensing layer when no strain is applied. The absolute value of the maximum resistance change rate during the charging and discharging process (|ΔR / R0|) is used to characterize the sensitivity of the in-situ monitoring device of each application example. The larger the absolute value of the maximum resistance change rate during the charging and discharging process, the greater the sensitivity of the in-situ monitoring device. The experimental results are shown in Table 4:

[0185] Table 4 Sensitivity of in-situ monitoring devices in various application examples

[0186] Thickness of hydrogel (mm) Sensitivity (|ΔR / R0|) Application Example 1 0.8 15.63 Application Example 2 1.6 6.21 Application Example 3 2.8 3.48

[0187] It can be seen from Table 4 that in the present invention, the in-situ monitoring device with a hydrogel of a specific thickness has better sensitivity, can detect the temperature or deformation of the fiber battery more accurately and in real time, and also has a longer service life.

[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A fiber battery, characterized in that: It includes a positive electrode, a negative electrode and a solid electrolyte, the solid electrolyte wraps the positive electrode and the negative electrode, the positive electrode and the negative electrode are both spiral in shape, the positive electrode is nested in the negative electrode, the positive electrode is a positive electrode wire with a manganese-based material on the surface, the negative electrode is a negative electrode wire with metallic zinc on the surface, and the manganese-based material contains manganese dioxide, a conductive agent, and a binder.

2. The fiber battery according to claim 1, characterized in that: Including at least one of the following (1)-(3): (1) The manganese-based material contains manganese dioxide, a conductive agent, and a binder in a mass ratio of (6-8):(1-2):(1-2); (2) The manganese-based material loading per unit area of ​​the positive electrode wire is 0.15-0.4 mg / cm 2 ; (3) The metal zinc loading per unit area of ​​the negative electrode wire is 3.0-20.0 mg / cm 2 .

3. The fiber battery according to claim 2, characterized in that: Including at least one of the following (1)-(3): (1) The manganese-based material contains manganese dioxide, a conductive agent, and a binder in a mass ratio of (7-8):(1-2):1; (2) The manganese-based material loading per unit area of ​​the positive electrode wire is 0.18-0.38 mg / cm 2 ; (3) The metal zinc loading per unit area of ​​the negative electrode wire is 4.0-18.0 mg / cm 2 .

4. The fiber battery according to claim 3, characterized in that: The ratio of the manganese-based material loading per unit area of ​​the positive electrode wire to the metal zinc loading per unit area of ​​the negative electrode wire is 0.2:(4.0-18.0).

5. The fiber battery according to claim 1, characterized in that: Including at least one of the following (1)-(4): (1) The solid electrolyte contains guar gum, zinc salt and manganese salt; (2) The conductive agent is at least one of carbon nanotubes, graphene, Super P, and acetylene black; (3) The binder is at least one of polyvinylidene fluoride, carboxymethyl cellulose and polyacrylic acid; (4) The material of the positive electrode wire and / or the negative electrode wire is at least one of stainless steel and carbon fiber.

6. A method for preparing a fiber battery according to any one of claims 1 to 5, characterized in that: The steps include: S1. Coating and / or spraying a manganese-based material on the surface of the positive electrode wire to obtain a positive electrode for standby use; S2. electroplating metal zinc on the surface of the negative electrode wire to obtain a negative electrode for standby use; S3. Wrap the positive electrode and the negative electrode with a solid electrolyte, and embed the positive electrode in the negative electrode to obtain a fiber battery.

7. Application of the fiber battery according to any one of claims 1 to 5 in wearable smart electronic products.

8. An in-situ monitoring device, characterized in that: It comprises the fiber battery and hydrogel according to any one of claims 1 to 5, wherein the surface of the fiber battery is provided with hydrogel.

9. The in-situ monitoring device according to claim 8, characterized in that: The thickness of the hydrogel is ≥0.8 mm.

10. A method for preparing the in-situ monitoring device according to any one of claims 8 to 9, characterized in that: The steps include: By wrapping the fiber battery with hydrogel, an in-situ monitoring device is obtained.

Citation Information

Patent Citations

  • Metal ion battery and preparation method thereof

    CN109950639A

  • High-capacity and high-rate flexible zinc ion battery and application thereof

    CN110429284A

  • Aqueous zinc-manganese battery fiber with dual-function protective layer and of fiber

    CN113036096A

  • Preparation method of high-performance fiber lithium ion battery based on gel electrolyte

    CN114759257A

  • Coaxial flexible solid-state battery structure and preparation method thereof

    CN116072887A